A Facile Method to Synthesize 3D Pomegranate-like Polydopamine Microspheres - Ghorbani, Farnaz; Ghalandari, Behafarid; Liu, Chaozong (Frontiers in Bioengineering and Biotechnology, 2021)
Nanospheres have found versatile applications in the biomedical field; however, their possible harmful effects on immune and inflammatory systems are also a crucial concern. Inspired by a pomegranate structure, we demonstrated a novel structure for the nanostructured microspheres to overcome the drawbacks of nanospheres without compromising their merits. In this study, 3D pomegranate-like polydopamine microspheres (PDAMS) were synthesized by self-oxidative polymerization of dopamine hydrochloride. Herein, controlling the pH during polymerization led to synthesizing homogeneous agglomerated nano-sized spheres (400-2000 nm) and finally forming tunable and monodisperse micron-sized particles (21 µm) with uniform spherical shape porous microstructure. PDAMS interaction with the potential targets, Bone morphogenetic protein-2 (BMP2), Decorin, and Matrilin-1, was investigated via molecular calculations. Theoretical energy analysis revealed that PDAMS interaction with BMP2, Decorin, and Matrilin-1 is spontaneous, so that a protein layer formation on the PDAMS surface suggests application in bone and cartilage repair. It was also observed that PDAMS presented in-vitro degradation within four weeks. Here, disappearance of the UV-VIS spectrum peak at 280 nm is accompanied by the degradation of catechol groups. Pomegranate-like PDAMS support the biomimetic formation of hydroxyapatite-like layers, making them appropriate candidates for hard tissue applications. Herein, the appearance of peaks in XRD spectrum at 31.37, 39.57, 45.21, and 50.13° attributed to hydroxyapatite-like layers formation. All these results demonstrated that self-oxidative polymerization under a controllable pH can be a green and straightforward technique for preparing the pomegranate-like PDAMS and providing an innovative basis for further pre-clinical and clinical investigations.